Cationic supercapacitance of carbon nanotubes covered with copper hexacyanoferrate. (26th September 2019) - Song, Fangfang; Huo, Da; Hu, Jianguo; Huang, Hong; Yuan, Junhua; Shen, Jianfeng; Wang, Ai-Jun
Abstract: Carbon nanotubes (CNT) are uniformly covered with copper hexacyanoferrate (CuHCF) via coprecipitation to form a core shell structure. The CuHCF thickness can be tuned from 10 nm to 30 nm by changing the CuHCF loading in the hybrids from 25% to 58%. The capacitive behavior is affected by the hydrated cation radius. In 1 mol l −1 KCl solution, CuHCF/CNT hybrids (46% CuHCF loading) show the largest specific capacitance of up to 989 F g −1 at a discharge density of 1 A g −1 . The hybrids also possess superior rate capability with only 8.2% capacitance loss when increasing the discharge current from 1 to 20 A g −1 . The superior capacitive performance of the hybrids in the K + -ion solution can be attributed to the smaller hydrated radius of the K + ion, which will favor the diffusion of the cation within the CuHCF lattice, leading to a larger faradic current. Besides, the cyclic stability of the hybrids is surprising, with 89.7% capacitance retention after 10000 discharge/charge cycles. The CuHCF/CNT hybrids are combined with the reduced graphene oxides (RGOs) to construct an asymmetrical supercapacitor, and its potential window can reach up to 2.0 V. More importantly, this supercapacitor exhibits a high energy density of 60.4 Wh kg −1 at the power density of 0.5 kW kg −1 .